Influência dos parâmetros de Processamento e da composição na morfologia de resinas ABS - Porcel, Fernanda da Silva (Universidade Federal de São Carlos, 2004)
The present work is about the influence of processing parameter and composition on the morphology of acrylonitrile-butadiene-styrene (ABS)resins. The ABS grades chosen are commercial products with high rubber content, i. e., above 40 wt%. A styrene-acrylonitrile copolymer (SAN) was blended to ABS parental compositions by melt extrusion in order to dilute the overall rubber contents, practice also used at the industry. The pure ABS in powder were processed in three different ways: compression, extrusion and injection molding. In each process there were variation of molding condition, and its influence on morphology formation were studied by transmission (TEM) and scanning (SEM) electron microscopy. Blends of SAN content 2.5, 5, 10, 20, 30 and even 50 wt% of SAN had their morphologies investigated. Besides that, the polymeric components of the blends were chemically, rheologically and thermo-mechanically characterized. The analysis showed how the grafting grade and the amount of free SAN on ABS can be critical on the rheological characteristics of these materials. The pure ABS morphology showed agglomerated rubber particles, big enough to become the system matrix phase. Changes on the processing parameters alter the morphology only on the disperse phase domains size and distribution. The SEM morphology analysis of injection molded samples showed enhanced rubbery phase particles agglomeration at the border regions of the specimen. Adding up to 30 wt% of SAN in ABS wasn t enough to promote phase inversion, yielding a SAN rich phase as the system matrix. This result suggests that the added SAN wasn t miscible into the ABS free SAN.
Influence of processing parameters and composition on the morphology of ABS resins
Keywords: Polímeros; Tenacificação; ABS; SAN; Blendas poliméricas; Morfologia de blendas; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA